Deconstruction of the character lydia bennet in jane austen’s pride and prejudice - Hayati, Rita ((JELE) Journal Of English Language and Education, 2017)
Pride and Prejudice is one of the greatest literary work. It is a story about the Bennets daughters’ love life. One of whom is Lydia Bennet, assumed as the antagonist, whose character is going to be deconstructed using Derrida theory of Deconstruction. The purpose of this research is to find out how the readers’ interpretation over a character in a story may be different from what has been expected by the author. The readers, however, may attack what has been structured hierarchically once they doubt about what it is written in the text. Since family is the first to shape a child’s behaviour, thus Lydia’s parents as well as her four older sisters are responsible for her misbehaviour.